A dinâmica interacional em um colégio da Brigada Militar: os rituais de interação, as vozes sociais e as fronteiras discursivas - Santos, João Ricardo Fagundes dos (2020)
This dissertation discusses the interactional dynamics of the Colégio Tiradentes da Brigada Militar - Passo Fundo/RS (CTBM-PF). Inserted in the line of research Constitution and Interpretation of the Text and Discourse of the Graduate Program in Letters at the University of Passo Fundo, the work presents as elements analyzed the interactions between students, teachers, civil and military servants, of the CTBM-PF, corpus this produced from the school's regulations and information from the researcher's field observations. The study is motivated by the possibility of discussing the interaction in the school, mainly in military schools, giving the necessary focus to the social, cultural and ideological elements that make up the discourse. Thus, based on Dialogic Discourse Theory (DDT), of the Circle of Bakhtin, the central objective of this study is to analyze the dialogical relations of ideological signs in the interactional dynamics of CTBM-PF, specifically in military interaction rituals, verifying the relationship of the use of these signs with the heteroglossic atmosphere dialogued in the social context of a military college and its tension of social forces and social voices. In order to fulfill this major objective, this work proposes: to observe the interaction rituals and the ideological signs present in the discourse of the subjects participating in the CTBM-PF interactional dynamics; to analyze the dialogical relations of the ideological signs and the social reality of the military college and with the social voices to which these signs are anchored; and demonstrate the meanings of the discourse in the observed interactions, in the relationship between the social context that gives meaning to the discourse and the use of ideological signs that shape the social context of the CTBM-PF, showing the clash of social forces and the dialogical tension of the encounter different social voices, which defines the dialogized heteroglossia. The theoretical axis that underlies this investigation addresses the social nature of language and the meanings of discourse, based on Volóchinov (2017) and Bakhtin (2011); the materialization of interaction in the form of rituals, with considerations by Goffman (2012); and the military school, which is the social sphere in which the analyzed interactions take place. The study is configured within the scope of the Dialogical Discourse Analysis, of the Circle of Bakhtin, in a case study with a qualitative approach, which seeks meaning in the interaction considering the socio-cultural influences of the context. In summary, the analysis proposes some results: the military rituals of interaction and the presence of subjects anchored in military voices are presented as strategies for monologizing the discourse, for centralizing interactions in the same social voices, in the word of authority; even with this attempt at monologization, the interactional dynamics in the CTBM-PF is based on a dialogized heteroglossia, that is, a sociocultural encounter of different social voices, generating dialogical tensions; therefore, the social role of the student and the teacher, in a military college like CTBM-PF, is to work on the borders, to know how to play the game of social powers that the school formulates, but also to enable dialogue and meeting the most different social voices that constitute the subjects of the interaction.